Software requirements analyst profile: A descriptive study of Brazil and Mexico - Calazans, Angelica (2019)
Software requirements analyst work is considered crucial in the software development lifecycle. This paper presents a descriptive study on the software requirements analyst profile, considering Brazilian and Mexican markets, two countries that lead IT investment ranking in Latin America. To identify the competences expected by the Brazilian and Mexican markets for software requirements professionals was the study objective. The competency model considers a set of knowledge, skills and attitudes. Content analysis and Nvivo software were used to categorize 311 job ads for software requirements analysts between 2016 and 2017. In terms of knowledge, the importance of higher education for both countries was identified. 'Using techniques and tools,' 'methodological competence,' 'good written communication,' and 'good verbal communication' were identified as relevant skills. The most important attitudes identified were: 'analytical thinking,' 'organization,' 'interpersonal relationship' and 'information sharing.' Most of results obtained confirm requirements analyst skills pointed out by other authors, but there are some differences due to the geographic context. At the same time, findings can help improve the understanding of different approaches in the requirements engineering field in the two countries and professionals working particularly in the Latin American market.